Promotion strategies of food delivery O2O supply chain considering service congestion effect with anti-food waste regulation - Xu, Guangye; Tang, Yan; Xu, Shiqi (Frontiers in Sustainable Food Systems, 2025)
Amidst the rapid expansion of the online-to-offline (O2O) food delivery sector, this paper investigates the promotion strategies employed by restaurants and food delivery platforms within the supply chain, and explores how these entities select promotion strategies under different conditions, including the intensity of government anti-food waste regulations, service congestion effect, and commission ratio, with the aim of improving profits and reducing food waste. Utilizing a game-theoretical approach, we focus on three primary promotion strategies: a no-promotion strategy (N strategy), a price discount strategy (D strategy), or a volume-based price discount strategy (S strategy). Our results reveal that the restaurant’s choice of promotion strategy is significantly correlated with the offline congestion effect, but not directly associated with anti-food waste regulations. Conversely, the platform’s optimal strategy and the extent of food waste are more closely related to the stringency of anti-food waste penalties. Under specific conditions, a win-win scenario can be achieved where both restaurants and platforms benefit economically while reducing food waste.